Breeding and Rearing Naked Mole-Rats (Heterocephalus glaber) under Laboratory Conditions - Yu, Chenlin (J Am Assoc Lab Anim Sci, 2017)
The unique biologic characteristics of naked mole-rats (NMR, Heterocephalus glaber) include longevity, cancer resistance, hypoxia tolerance, and pain insensitivity, making NMR an attractive model for biomedical research on aging, cancer, and neurobiology. However, breeding and rearing NMR in captivity is challenging. Here, we report a method for breeding NMR by using a closed-colony mating system. We selected sexually mature male and female NMR from different natal colonies and mated them 1:1. The 5 original colonies had an annual parity of 3.20 ± 0.84 (mean ± 1 SD), with 38.80 ± 9.50 pups born, 33.80 ± 8.32 pups weaned, and a survival rate of 87.19% ± 6.09% after weaning. The average annual parity of 22 N1 pairs (established from the progeny of the 5 original pairs) was 3.09 ± 0.81, with 34.86 ± 10.66 total pups born during the year, 30.14 ± 10.23 pups weaned, and a survival rate after weaning of 85.51% ± 6.60%. The average annual parity of 29 N2 pairs (that is, offspring of N1 pairs) was 3.04 ± 0.87, with 33.69 ± 11.42 pups born, 28.17 ± 10.43 pups weaned, and a survival rate after weaning of 83.66% ± 10.75%. None of these measures differed among the 3 generations, with average reproductive success exceeding 70% for each. In addition, the reproduction and growth of the N1 and N2 generations was similar to the original colonies. Our breeding method remarkably increases the production of NMR, thus representing a great potential to promote experimental NMR research and its applications.